Upaya Meningkatkan Kebugaran Jasmani Siswa Kelas V Sekolah Dasar Negeri 2 Bajulan Kecamatan Loceret Kabupaten Nganjuk Tahun Ajaran 2024/2025 - Bima Kukuh Dwi Pamungkas; Mohammad Nur Kholis; Riyan Asrul Unus; Vaza Deefath Az Azka; Dwi Fany Prayoga; Aditya Sukma Ramadhan; Dewi Yuliana (Jurnal Simki Postgraduate, 2024)
Physical education is basically an indispensable part of the overall education system. The purpose of physical education is not only to develop the physical realm, but also to develop aspects of health, physical fitness, critical thinking skills, emotional stability, social skills, reasoning and ethical actions through physical activity and sports. Based on the description above, the author conducted a study entitled Efforts to Improve Physical Fitness through a Play Approach in Physical Education Learning for Grade V Students in PJOK Learning at Elementary School SD Negeri 2 Bajulan, Loceret District, Nganjuk Regency. The research conducted was Classroom Action Research. The test results for November 20, 2024 after learning using the game approach, the results in cycle I for male students increased to 2.15 "while for female students increased to 2.21", while the results on November 27, 2024 in Cycle II male students increased to 2.12 "and for female students increased to 2.17". Thus it can be concluded that students' abilities in mastering the material in this case physical fitness learning through the approach of playing moving keys and catching criminals can improve the physical fitness of class V students at Elementary School 2 Bajulan, Loceret District, Nganjuk Regency with a 600 m running test.